Basics Malaysian Sign Language: the development of mobile learning application - Mohamed, Juliana; Salim, Nur Irdina Izzaty; Jamil, Eryna Misya; Mohd Nazri, Ainnur Nazeera; Abdul Hamid, Mariam; Mohamed Ali @ Md Hani, Mohd Hatta; Md Yasin, Mohd Suhaimi; Jofri, Muhamad Hanif (Multidisciplinary Applied Research and Innovation, 2020)
Sign language can be difficult for citizen who wants to learn and communicate with deaf people. Lack of a right resources and platforms demanding people to know and learn. A mobile learning application called Basics Malaysian Sign Language was developed to address of this issue which enable user to learn basic sign languages and basic conversation. ADDIE model were used to implement the project. The application gives a positive effects especially for beginner user to assist the community in learning sign language. As a result, the community can communicates with each other especially to deaf people.